Types of intelligence, ethics and time budget pressure on auditor performance - I Dewa Made Endiana; Putu Diah Kumalasari (Journal of Applied Sciences in Accounting, Finance, and Tax, 2024)
Auditor performance is the result of work completed by an auditor in carrying out the tasks assigned to him. It depends on the auditor's skill, experience, and commitment to the task at hand. Good auditor performance can be produced if an auditor is able to pay attention to the factors that can influence it. Intellectual intelligence, emotional intelligence, spiritual intelligence, work ethics, and time budget pressure are several factors that can influence auditor performance. With the inconsistencies that occur in the results of research that has been conducted, this research aims to re-examine the influence of intellectual intelligence, emotional intelligence, spiritual intelligence, work ethic, and time budget pressure on the performance of auditors at public accounting in Bali. This research was conducted at 19 public accounting in Bali. The sampling technique used is a saturated sampling technique, which is a technique for determining a sample if all members of the population are used. Respondents in this research were 71 auditors, consisting of junior auditors, senior auditors, and managers. The data analysis technique used is the multiple linear regression analysis technique. The research results show that intellectual intelligence, emotional intelligence, and spiritual intelligence have no effect on auditor performance. Meanwhile, work ethic and time budget pressure have a positive effect on auditor performance.